Prensa local y radicalización política ciudadana: el diario asturiano El Comercio hacia la guerra civil - Muñiz Sánchez, Jorge (Estudios sobre el Mensaje Periodístico, 2007)
Since the First World War the journal El Comercio, like others, starts an authoritarian right-wing drift that goes from reforming plans to the praise of the dictatorship. The fear of a revolution of the social sectors represented by the newspaper was the reason of this change. One of its consequences, the contribution to the polarization environment that became breeding ground for the civil conflict. The investigation of the fundamental landmarks of this particular evolution contributes to understand the role of the press at that time in Asturias and it is a reflection about its responsability in citizens’ education.